Migrant and Diasporic Film and Filmmaking in New Zealand - Zalipour, Arezou; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book is the first ever collection on diasporic screen production in New Zealand. Through contributions by a diverse range of local and international scholars, it identifies the central characteristics, histories, practices and trajectories of screen media made by and/or about migrant and diasporic peoples in New Zealand, including Asians, Pacific Islanders and other communities. It addresses issues pertinent to representation of migrant and diasporic life and experience on screen, and showcases critical dialogues with directors, scriptwriters, producers and other key figures whose work reflects experiences of migration, diaspora and multiculturalism in contemporary New Zealand. With a foreword by Hamid Naficy, the key theorist of accented cinema, this comprehensive collection addresses essential questions about migrant, multicultural and diasporic screen media, policies of representation, and the new aesthetic styles and production regimes emerging from New Zealand film and TV. Migrant and Diasporic Film and Filmmaking in New Zealand is a touchstone for emerging work concerned with migration, diaspora and multiculturalism in New Zealand's screen production and practice.
Foreword by Hamid Naficy -- Preface by Annie Goldson -- Introduction Migration histories and screen representations in New Zealand -- Section I. Representations and production -- Chapter 1 Vincent Ward: Migrancy, Exile and Colonial Trauma -- Chapter 2 Kiwi Dragons in Love: The Chinese Diaspora and New Zealand Interracial Screen Romances -- Chapter 3 In/visible Subjects: Diasporic and Multicultural Identities in Zia Mandviwalla's Short Films -- Chapter 4 Multiculturalism in No.2: Representing New Zealand in Sight and Sound -- Chapter 5 Circulating Currents: Disaporic Intensification and the Films of Tusi Tamasese -- Chapter 6 Fitting the Screen: Intermittent Production Practices and Diasporas in New Zealand -- Chapter 7: Bringing us All Together: Multiculturalism as Neoliberalism through New Zealand on Air -- Section II. Behind the Lens: A look inside the New Zealand screen industry -- Chapter 8 Shuchi Kothari (Indian Background) -- Chapter 9 Zia Mandviwalla (Indian background) -- Chapter 10 Sima Urale (Samoan background) -- Chapter 11 Tusi Tamasese (Samoan background) -- Chapter 12 Roseanne Liang (Chinese background) -- Chapter 13 Stephan Kang (Korean background) -- Conclusion Diasporising Screen.
Keywords: Emigration and immigration; Motion pictures; Television broadcasting; Culture; Australasia; Diaspora Studies; Film and Television Studies; Australasian Culture